An Analysis of Turkish Pre-Service Teachers' Knowledge of Autism Spectrum Disorder: Implications for Teacher Preparation Programs. (September 2016) - Rakap, Salih; Balikci, Serife; Parlak-Rakap, Asiye; Kalkan, Sinan
The purpose of the present study was to investigate knowledge of autism among teacher candidates who are likely to have the initial contact with children with autism within public school system in Turkey. Five hundred and four senior pre-service teachers who were enrolled in four different teacher education programs participated in the study. Data were collected using a survey package at the end of spring semester during the last year of college. Results indicated that pre-service teachers across programs had limited knowledge of autism and its characteristics. Findings of the present study call for the development of pre- and in-service training programs for teachers of children with autism. Further implications of findings for future research and practice are discussed.